Toll‐like receptor 4 attenuates a murine model of atopic dermatitis through inhibition of langerin‐positive DCs migration. Issue 9 (20th July 2018) - Lin, Lin; Xie, Mengying; Chen, Xi; Yu, Yu; Liu, Yunzhi; Lei, Ke; Wang, Di; Zeng, Jiaqi; Zhou, Jia; Zhang, Liyun; Zuo, Daming; Sun, Ledong
Abstract: Atopic dermatitis (AD) is a common chronic inflammatory skin disease that is often associated with skin barrier dysfunction leading to a higher frequency of bacterial and viral skin infections. Toll‐like receptor (TLR) 4 on resident skin cells was involved in sensing pathogens and eliciting pathogen‐specific innate and adaptive immune responses. Previous studies have demonstrated that TLR4 was linked to AD severity in context of pathogen infection. However, the immune regulatory role of TLR4 in AD remains to be defined. We here investigated the immune regulatory function of TLR4 in AD induced by repeated epicutaneous application of a hapten, 2, 4‐dinitrochlorobenzene (DNCB). Our results showed that TLR4‐deficient (TLR4 −/− ) mice exhibited more severe AD symptoms than WT mice after DNCB challenge. The DNCB‐treated TLR4 −/− mice also displayed higher expression levels of inflammatory cytokines and stronger Th2 response than WT counterparts. Moreover, the skin expression of thymic stromal lymphopoietin (TSLP), an important potential contributor to allergic inflammation, was significantly elevated in TLR4 −/− mice compared with that in WT mice upon DNCB administration. Furthermore, we demonstrated that the migration of langerin‐positive dendritic cells (DCs) into draining lymph nodes was enhanced in TLR4 −/− mice following DNCB challenge, which is partially dependent on the production of pro‐inflammatory cytokine TNF‐α. Together, these results determined that TLR4 affected the hapten‐induced skin inflammation in the absence of exogenous pathogen infection, suggesting that TLR4 not only regulates infection but also may serve as a modulator of the immune response during AD development.